Analisis Pembelajaran IPA Berbasis SETS Terinterasi Kearifan Lokal dengan Microlearning - Tutik Yuliatun; Anderias Henukh; Don Jaya Putra; Ika Trisni Simangunsong; Susanti Susanti (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
To keep pace with the Industrial Revolution 4.0, students require teacher guidance to maintain a foundation rooted in local wisdom. This can be achieved through various approaches, such as SETS-based (Science, Environment, Technology, and Society) science instruction integrated with local wisdom and microlearning. Local wisdom serves as a means to balance the rapid advancement of science and technology. This study aims to analyze the implementation of SETS-based science instruction—integrated with local wisdom and microlearning—in junior high schools (SMP and MTs) in Merauke. A descriptive qualitative research method was employed, utilizing a questionnaire comprising 16 statements. The study involved 23 science teachers from SMP and MTs schools in Merauke. Data analysis using descriptive statistics revealed that 76% of respondents had never implemented SETS-based science instruction integrated with local wisdom, 68% did not understand the concept of microlearning, and 89% expressed interest in implementing SETS-based science instruction that integrates local wisdom and microlearning. Respondents also outlined plans to implement science instruction that combines technology, local wisdom, and interactive learning methods.